Efecto de atazanavir y del extracto acuoso de chenopodium quinoa sobre la lipoperoxidación de membranas eritrocíticas en pacientes seropositivos a VIH - Asmat Marrufo, Percy Esteban (2013)
ABSTRACT There was studied the In vitro effect of the watery extract of Chenopodium quinoa "Quinua" and of Atazanavir, in the lipoperoxidación in membranes eritrocíticas of patients with the virus of human immunodeficiency seropositive (HIV) without administration of anti-retroviral. 5 were extracted ml from blood of every patient and for the design of the workgroups every sample was exposed to each of the following substances: group control (saline solution bufferada), and groups problem 1, 2 and 3; Atazanavir 1.2 ug/ml, I summarize of Chenopodium quinoa 7.5 % P/V and Atazanavir 1.2 ug/ml associated with Chenopodium quinoa 7.5 % P/V respectively. The concentrations decided of malondialdehido in membranes eritrocitarias, across the method TBARS (Species you reactivate for the acid tiobarbitúrico). One concludes that so much the watery extract of the Quinua and since of Atazanavir the levels diminish of malondialdehido in membranes eritrocíticas in patient HIV without administration of anti-retroviral (p˂0.05).